(untitled) (Indian Journal of Animal Production and Management, 2024)
The present experiment was conducted with objective to study effect of water restriction (WR) and rehydration on body weight, feed and nutrient intake in indigenous hoggets under intensive production system during summer season. Eighteen farm born unshorn Patanwadi and Marwari breeds of hoggets were selected and randomly divided in three treatment groups on the basis of body weight (25 - 30 kg) comprising of six in each group, viz., T1: Control (ad.lib.water), T2: (WR1-20% water restriction), T3: (WR2- 40% water restriction) for 28 days of water restriction and 4 days of rehydration. The body weight (kg), dry matter (g/d, % and g/kg W0.75), digestible crude protein (g/d, % and g/kg W0.75) and total digestible nutrient (g/d, % and g/kg W0.75) intake of experimental animals were comparable among treatment groups. The body weight, dry matter and nutrient intake of experimental animals recovered significantly after 2nd day of rehydration. The results indicated that the Patanwadi and Marwari hoggets can withstand up to 40% water restriction during summer season under intensive production system